2023
DOI: 10.1245/s10434-023-14216-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sodium Thiosulfate on Prevention of Nephrotoxicities in HIPEC: An Ancillary Evaluation of Cisplatin-Induced Toxicities in Ovarian Cancer

Rosemary N. Senguttuvan,
Nicole Lugo Santiago,
Ernest S. Han
et al.

Abstract: Purpose Hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin confers a survival benefit in epithelial ovarian cancer (EOC) but is associated with renal toxicity. Sodium thiosulfate (ST) is used for nephroprotection for HIPEC with cisplatin, but standard HIPEC practices vary. Methods A prospective, nonrandomized, clinical trial evaluated safety outcomes of HIPEC with cisplatin 75 mg/m2 during cytoreductive surgery (CRS) in patients with EOC (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The authors’ single-institution experience of HIPEC with and without ST demonstrated the magnitude of renal morbidity with cisplatin and quantified the mitigation of nephroprotection by ST. 5 In their prospective pilot trial of 40 ovarian and endometrial cancer patients undergoing cisplatin HIPEC, they demonstrated that the addition of ST resulted in a reduction of renal toxicity from 33 to 0%. None of the patients treated with ST in their study experienced renal toxicities, whereas the patients without ST treatment were affected by grades 2 and 3 acute and chronic kidney injuries.…”
Section: Presentmentioning
confidence: 99%
“…The authors’ single-institution experience of HIPEC with and without ST demonstrated the magnitude of renal morbidity with cisplatin and quantified the mitigation of nephroprotection by ST. 5 In their prospective pilot trial of 40 ovarian and endometrial cancer patients undergoing cisplatin HIPEC, they demonstrated that the addition of ST resulted in a reduction of renal toxicity from 33 to 0%. None of the patients treated with ST in their study experienced renal toxicities, whereas the patients without ST treatment were affected by grades 2 and 3 acute and chronic kidney injuries.…”
Section: Presentmentioning
confidence: 99%